Breast cancer stromal clotting activation (Tissue Factor and thrombin): A pre‐invasive phenomena that is prognostic in invasion - Hudhaifah Shaker; Nigel J. Bundred; Göran Landberg; Susan A. Pritchard; Harith Albadry; Sarah L. Nicholson; Lauren J. Harries; Jing Y. E. Heah; John Castle; Cliona C. Kirwan (Cancer Medicine, 2020)
Abstract Background Tumor stroma, of which fibroblasts are the most abundant cell, resembles a non‐healing wound, where a procoagulant environment creates a permissive milieu for cancer growth. We aimed to determine if tumor expression of coagulation factors (procoagulant phenotype), and systemic hypercoagulability, occur at the preinvasive (ductal carcinoma in situ; DCIS) stage and correlate with breast cancer subtype, disease‐free survival (DFS), and overall survival (OS). Methods In a prospective cohort of early breast cancer (DCIS, n = 76; invasive, n = 248) tumor, normal breast and plasma were examined. Fibroblast and epithelial expression of Tissue Factor (TF), thrombin, PAR1, PAR2, and plasma thrombin‐antithrombin (TAT) and D‐dimer were correlated with clinicopathological data, and 5‐year survival. Results Fibroblast expression of TF, thrombin, and PAR1 was increased in DCIS and invasive cancer compared to normal breast fibroblasts (P ≤ .003, all). Fibroblast TF, thrombin, PAR1, and PAR2 was increased in cancers with high Ki67, high grade, ER‐ (vs ER+), and HER2+ (vs HER2‐) (all P < .05). On univariate analysis, fibroblast TF expression was inversely associated with DFS (P = .04) and OS (P = .02). D‐dimer was higher in node positive (507 (CI: 411‐625) ng/mL, n = 68) vs negative patients (428 (CI: 387‐472) ng/mL, n = 171, P = .004) and inversely associated with OS (P = .047). On multivariate analysis, plasma TAT was associated with reduced OS (HR 3.26, CI 1.16‐3.1, P = .02), with a high plasma TAT (≥3.2 ng/mL) associated with > 3‐fold mortality risk compared to low TAT. Conclusion This demonstrates procoagulant phenotypic changes occur in fibroblasts at the preinvasive stage. Fibroblast procoagulant phenotype is associated with aggressive breast cancer subtypes and reduced survival. Coagulation may be a therapeutic target in breast cancer.